Противоречия и поиски 60-70-х годов - Хайт Владимир Львович (1983)
Экземпляры: ИСК (20120423) / Инвентарный номер: 804992 / Цена: 2.70 / Сис.шифр: 85.113(3/8) / Авт.знак: А 87 / ГРНТИ: 67 / ББК: 85.113(4)